Renal replacement therapy as a therapeutic option for right heart failure in severe pulmonary arterial hypertension - Mai Shimbo; Masaru Hatano; Satoshi Ishii; Akihito Saito; Hiroki Yagi; Shun Minatsuki; Hisataka Maki; Eisuke Amiya; Norifumi Takeda; Issei Komuro (ESC Heart Failure, 2022)
Abstract Pulmonary arterial hypertension (PAH) is a progressively life‐threatening disease that causes right heart failure (RHF). Renal dysfunction frequently complicates PAH with RHF and is associated with a worse prognosis. Renal replacement therapy (RRT) may be a therapeutic option, although its efficacy and safety are unclear. We describe a 30‐year‐old male with severe PAH who developed renal insufficiency and diuretic‐refractory volume overload complicated with RHF but was successfully managed with intermittent RRT via a subcutaneously fixed superficial artery for 4 years. RRT led to haemodynamic stability, which enabled us to carefully de‐titrate parenteral PAH drugs without worsening RHF. This case highlights that RRT may be a potential alternative for haemodynamic and volume control of refractory fluid retention complicated with RHF in severe PAH cases. Further studies are warranted to gain more insight into patient selection and the optimal timing of RRT in PAH patients with deteriorating RHF.